Revisiting the Determinants of Capital Flows to Emerging Markets : A Survey of the Evolving Literature - Hannan, Swarnali (IMF Working Papers; Working Paper ;, 2018)
This paper documents the evolution of gross and net capital flows to emerging market economies and surveys the large literature on the potential drivers. While the capital flow landscape has been shaped by the evolution of both global and country-specific factors, the relative importance of these factors has varied over time and differs depending on the type of capital flows. The findings from the survey of the literature thus underscores the importance of policies in both source and recipient countries in shaping capital flows.